Take Off 4-Health: Innovative Strategies to Improve Wellness in Adolescents - Harris, Nancy G.; Briley, Alexis; Collier, David N.; Dunn, Carolyn Kusbit; Crawford, Yancey; Henes, Sarah T.; Kinner, Stephanie; Kolasa, Kathryn M.; Lutes, Lesley D.; Scripture, Lee (My University, 2010)
Summer camps for weight loss are popular. We present the nutrition curriculum for a 3 week residential camp for adolescents with health risks related to obesity or type 2 diabetes. The curriculum includes a camper meal card, six lessons based on strategies associated with healthy weight, meal time tips and more. Formative evaluation was completed. Curriculum is available at www.ecu.edu/pedsweightcenter
The team included members from the Brody School of Medicine, the ECU Departments of Nutrition and Dietetics, Physical Therapy, Clinical Psychology, Medical Family Therapy and the NC Cooperative Extension Family and Consumer Sciences adn 4H Programs.
Keywords: Residential camp; Adolescent obesity; Nutrition education